(untitled) (The Insight, 2024)
Introduction: Appendicitis is the most common surgical abdominal emergency worldwide, and laparoscopic appendectomy is the preferred treatment for it. Objective: The objective of this study is to find clinical outcomes comparing laparoscopic and open appendectomy in terms of complicated appendicitis. Methods & Materials: A comparative study was conducted on 50 patients with complicated appendicitis, aged 20-45, treated between 2019 and 2023 at Sheikh Sayera Medical College, Gopalganj, Bangladesh. Data analyzed included pain location, appendicitis stage, concomitant diseases, surgical method, antibiotic prophylaxis, surgery duration, postoperative pain, complications, and mortality. Results: In the LA group, the operative time was 60.30 ± 10.30 minutes, with one case of bleeding and ICU admission each, no mortalities, and three intraoperative complications. The mean hospital stay was 1.10 ± 0.26 days. Oral analgesics were given for 3.05 ± 0.66 days, and parenteral for 1.04 ± 0.24 days. There were seven postoperative complications, with surgical site infection being the most common (three cases). In the OA group, the operative time was 45.84 ± 15.20 minutes, with four cases of bleeding, one ICU admission, no mortalities, and five intraoperative complications. The mean hospital stay was 5.00 ± 0.29 days. Oral analgesics were administered for 3.68 ± 0.40 days, and parenteral for 1.23 ± 0.56 days. Postoperative complications included ten cases, with surgical site infection (four cases) and intrabdominal abscess (two cases) being most common. Conclusion: This study demonstrated that laparoscopic appendectomy yields better clinical outcomes in treating patients with appendicitis compared to open surgery.